Reactive Oxygen Species (ROS) Play a Critical Role in the cAMP-Induced Activation of Ras and the Phosphorylation of ERK1/2 in Leydig Cells - Tai, Ping (Endocrine Society, 2011)
Activation of the LH receptor (LHR) in Leydig cells results in the phosphorylation of ERK1/2 by cAMP-dependent and cAMP-independent pathways. Here we examine the mechanisms by which cAMP stimulates ERK1/2 phosphorylation. We show that the stimulation of steroidogenesis is not necessary or sufficient to stimulate the phosphorylation of ERK1/2 but that other cAMP-dependent mitochondrial functions are involved. Using MA-10 cells as a model, we showed that cAMP analogs increase reactive oxygen species (ROS) formation and that an uncoupler of oxidative phosphorylation and a ROS scavenger prevent this increase. These two compounds also inhibit the increase in ERK1/2 phosphorylation provoked by cAMP analogs, thus suggesting that the cAMP-induced phosphorylation of ERK1/2 is mediated by mitochondrial ROS. In agreement with this hypothesis we also show that a reduction in glutathione levels, which alters the redox state of MA-10 cells, potentiates the effect of cAMP on ERK1/2 phosphorylation. Measurements of the dephosphorylation of ERK and the activation of Ras showed that the ROS scavenger prevents the cAMP-provoked activation of Ras and that cAMP, with or without a ROS scavenger, has little or no effect on the dephosphorylation of ERK. Lastly, we show that the uncoupler of oxidative phosphorylation and the ROS scavenger also prevent the ability of cAMP analogs to increase ERK1/2 phosphorylation in primary cultures of mouse Leydig cells. We conclude that, in Leydig cells, cAMP enhances the phosphorylation of ERK1/2 via a mitochondria-derived, ROS-dependent activation of Ras.